In situ picosecond transient diffuse reflectance spectroscopy of opaque TiO2 systems under microwave irradiation and influence of oxygen vacancies on the UV-driven/microwave-assisted TiO2 photocatalysis1. Issue 23 (21st June 2015) - Horikoshi, Satoshi; Tsutsumi, Hideya; Matsuzaki, Hiroyuki; Furube, Akihiro; Emeline, Alexei V.; Serpone, Nick
<x xml:space="preserve">Abstract</x> Effect of microwave radiation on pristine TiO2 and oxygen-vacancy rich titania, Vo-TiO2.